A basis for music education - Swanwick, Keith (NFER-Nelson Publ. Co., Reprinted by Routledge, 1979)
Designed for all music teachers, this book provides a careful and clear examination and analysis of the fundamental concepts involved in music. Professor Swanwick investigates questions such as: What is music? Is music meaningful? Does music refine our feelings and emotions? If so, how? The discussion of these questions forms a conceptual framework which will motivate further thinking and development in music education.